Silver Lining of Haze: The Mixed Effect of Haze on Donation - Li, Shihao; Fu, Guoqun; Yuan, Jingting; Wu, Jingyu (Frontiers in Psychology, 2020)
Considering the increasing frequency of haze hitting China, and its remarkably adverse impacts on society, this research aims to use 2 studies to explore the mixed effect of haze on donation behavior. Study 1: 110 participants were included into a weather information survey in which half of them were instructed to read haze weather information, and the other half were assigned to good weather information condition. After reading and recalling experiences under the same weather condition, all participants were displayed and asked to report their attitudes on a donation program, including their donation intention with money and time, the amount of donating money, and the behavior measurement about whether they would like to leave their email addresses to the charity organization to keep in further connection. The results showed people in haze weather condition, compared to whom in good weather condition, were more likely to donate money and less likely to donate time to the donation program. There is a significant interaction effect between haze or not and donation type on donation intention. We did not find effect of haze on the amount of donation and donating behavior. Study 2: 101 participants were randomly assigned to haze weather condition or good weather condition first and then were asked to judge a donation program as Study 1. After that, we measured mortality salience using three items as our mediator variable. The results showed there was a significant interaction effect between haze (vs. good) weather and donation type on donation intention which replicated the results of Study 1. People in haze condition would donate more money and less time compared to people in good weather condition. Besides, we proved mortality salience was the underlying mechanism. People in haze condition perceived higher level of mortality salience, which altered their attitudes upon money and time resources. Across two studies, we found convergent evidence supporting our hypotheses. Especially, haze weather can increase donation intention with money resources but decrease donation intention with time resources. This effect is mediated by mortality salience caused by haze. Based on our results, we conclude with an exploratory discussion.